1992
DOI: 10.1002/ajh.2830390317
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine therapy for thrombotic thrombocytopenic purpura

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a rare disorder characterized by microangiopathic haemolytic anemia, consumption thrombocytopenia, renal impairment, neurological dysfunction, and fever, but all these features are not present in every patient. Although the prognosis of TTP has improved since it was demonstrated that large volumes of fresh frozen plasma (FFP) lead to a remission in most patients, the disease remains fatal in many instances. Therefore, other therapies are often used in TTP, but there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…The platelet count began to increase reaching 65,000 /mm³ after 3 days of starting VCR and 175,000 /mm³ after 8 days. The total dose of VCR given to the patient was 4 mg without apparent side effects and this agrees with some studies using doses ranging from 2 mg up to 14 mg (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Ziman et al, reported 100 percent survival in their retrospective data of 12 TTP patients (PLT counts ranging 4,000/mm³ to 36,000/mm³) treated with standardized protocol of PE and VCR without side effects.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The platelet count began to increase reaching 65,000 /mm³ after 3 days of starting VCR and 175,000 /mm³ after 8 days. The total dose of VCR given to the patient was 4 mg without apparent side effects and this agrees with some studies using doses ranging from 2 mg up to 14 mg (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Ziman et al, reported 100 percent survival in their retrospective data of 12 TTP patients (PLT counts ranging 4,000/mm³ to 36,000/mm³) treated with standardized protocol of PE and VCR without side effects.…”
Section: Discussionsupporting
confidence: 69%
“…Successful vincristine use has been described in various small studies and case reports, usually as a rescue therapy in refractory TTP [17,[24][25][26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, complementary treatments, including immunosuppressive agents (corticosteroids, vincristine, cyclophosphamide, azathioprine, cyclosporine A), high-dose intravenous immunoglobulin (Ig), staphylococcal protein A immunoadsorption, and splenectomy, have been proposed. [7][8][9][10][11] Despite all these therapeutic options, about one third of all patients with acquired TTP develop multiple relapses or persistent disease. 1 The prediction of which patients are at high risk of either prolonged course or short-or long-term relapses remains a challenging issue.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to corticosteroids, immune modulating agents such as vincristine, cyclosporin, azathioprine, intravenous immunoglobulin, and staphylococcal protein A adsorption column therapy have been reported to be effective in some patients [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%